Rate or Rhythm Control in Older Atrial Fibrillation Patients: Risk of Fall‐Related Injuries and Syncope. Issue 10 (24th July 2019) - Dalgaard, Frederik; Pallisgaard, Jannik L.; Numé, Anna‐Karin; Lindhardt, Tommi Bo; Gislason, Gunnar H.; Torp‐Pedersen, Christian; Ruwald, Martin H.
Abstract : OBJECTIVES: Management of atrial fibrillation (AF) with rate and/or rhythm control could lead to fall‐related injuries and syncope, especially in the older AF population. We aimed to determine the association of rate and/or rhythm control with fall‐related injuries and syncope in a real‐world older AF cohort. DESIGN: A retrospective cohort study. SETTING: Danish nationwide administrative registries from 2000 to 2015. PARTICIPANTS: A total of 100 935 patients with AF aged 65 years or older claiming prescription of rate‐lowering drugs (RLDs) and/or anti‐arrhythmic drugs (AADs) were included. We compared the use of rate‐lowering monotherapy with rate‐lowering dual therapy, AAD monotherapy, and AAD combined with rate‐lowering therapy. MEASUREMENTS: Outcomes were fall‐related injuries and syncope as a composite end point (primary) or separate end point (secondary). RESULTS: In this population, the median age was 78 years (interquartile range [IQR] = 72‐84 y), and 53 481 (53.0%) were women. During a median follow‐up of 2.1 years (IQR = 1.0‐5.1), 17 132 (17.0%) experienced a fall‐related injury, 5745 (5.7%) had a syncope, and 21 093 (20.9%) experienced either. Compared with rate‐lowering monotherapy, AADs were associated with a higher risk of fall‐related injuries and syncope. The incidence rate ratio (IRR) for the composite end point was 1.29 (95% confidence interval [CI]: 1.17‐1.43) for AAD monotherapy and 1.46 [95% CI = 1.34‐1.58] for AAD combined with rate‐lowering therapy. When stratifying by individual drugs, amiodarone significantly increased the risk of fall‐related injuries and syncope (IRR = 1.40 [1.26‐1.55]). Compared with more than 180 days of rate‐lowering monotherapy, a higher risk of all outcomes was seen in the first 90 days of any treatment; however, the greatest risk was in the first 14 days for those treated with AADs. CONCLUSION: In AF patients aged 65 years and older, AAD use was associated with a higher risk of fall‐related injuries and syncope, and the risk was highest within the first 14 days for those treated with AADs. Only amiodarone use was associated with a higher risk. J Am Geriatr Soc 67:2023–2030, 2019 Abstract : See related editorial by Michael Rich .